(untitled) (Western European Journal of Historical Events and Social Science, 2025)
This article shows that the "Military Communism" policy introduced by Soviet Russia in 1918-1921 emerged as a unique system of country management during the civil war. This policy was also implemented in the Turkestan region and had a profound impact on the socio-economic life of the region. Its essence was as follows. All industrial production was concentrated in the hands of the state and managed on the basis of strict centralization; farmers handed over the surplus of their own produce to the state (food distribution, i.e. distribution); and the state took over the distribution of food and industrial products; the market disappeared and money circulation was replaced by kind (products); all able-bodied population was recruited into forced labor (militarization of labor)